2017
DOI: 10.1016/j.repc.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced degradation of HIF-1α contributes to impaired response of cardiomyocytes to hypoxia

Abstract: Taken together, the results obtained in this study suggest that MGO compromises the ability of cells to adapt to low oxygen tensions, by stimulating the degradation of HIF-1α, likely contributing to the development of diabetes-associated cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Indeed, in a low oxygen environment, HIF1α deficiency results in cell death 40 . The accumulation of MGO under hyperglycemia and the subsequent degradation of HIF1α are proposed as mechanisms underlying the detrimental effects of high glucose on various injuries, 41 such as hypoxic cardiomyocyte injuries 42 . MGO modifies HIF1α at its proline residues, leading to ubiquitination by the C-terminus of the HSC70-interacting protein (CHIP) and subsequent proteasome-dependent degradation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a low oxygen environment, HIF1α deficiency results in cell death 40 . The accumulation of MGO under hyperglycemia and the subsequent degradation of HIF1α are proposed as mechanisms underlying the detrimental effects of high glucose on various injuries, 41 such as hypoxic cardiomyocyte injuries 42 . MGO modifies HIF1α at its proline residues, leading to ubiquitination by the C-terminus of the HSC70-interacting protein (CHIP) and subsequent proteasome-dependent degradation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The next level of diabetes-induced deregulation of HIF-1 signaling involves responses to hypoxia. Experiments with cells cultured in an environment combining hyperglycemia and hypoxia show increased degradation of the HIF-1α protein ( 70 , 71 ). Thus, diabetes not only causes hypoxia but also compromises HIF-1 signaling.…”
Section: Hif-1 Signaling In Diabetesmentioning
confidence: 99%
“…Diabetes is known to impair microvasculature ( 129 , 130 ); particularly, diabetic cardiomyopathy is associated with a loss of coronary capillaries that further increases tissue hypoxia ( 131 ). Since the combination of hypoxia and hyperglycemia increases degradation of the HIF-1α protein ( 70 , 71 ), the ability of the diabetic heart to respond to hypoxic conditions is compromised ( 101 ). Consistent with these data are experiments with altered HIF-1 signaling in mouse hearts.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Compatible with this suggestion is the finding that knockdown of glyoxalase-1 in non-diabetic mice results in renal lesions indistinguishable from those of diabetic mice, while overexpression of glyoxalase-1 in diabetic mice prevents the development of nephropathy 18 . Other studies have shown that MGO impairs HIF-1α degradation and signaling 19,20 and activates AMPK mediated autophagic degradation of thioredoxin 1 21 , thus emphasizing its influence on redox homeostasis 22 . Despite the clear association between reactive carbonyl species and diabetic complications, their mode of action on endothelial cells is discussed ambiguously 2327 .…”
Section: Introductionmentioning
confidence: 97%